Rooms recommendation and reservation system for Unit Kokurikulum UiTM Melaka using rule based techniques / Mohd Ruhaifi Zainol - Zainol, Mohd Ruhaifi (2017)
Unit Kokurikulum is given authority to manage the room to reserve inside the Pusat Persatuan Pelajar(PPP) building. Conventional method to reserve the room now is using manual method, which is students need to come to PPP building regularly to check the availability of room to reserve. Students also need to fill in the form to reserve in the paper. Then students need comeback again to check the status of reservation, this system lack of efficiency in term of time management. Also for new students, they do not know which room is suitable for them to reserve to use. Rooms Recommendation and Reservations System for Unit Kokurikulum is a web-based application that help students with above problems. This system can give suggestion to students what suitable room to reserve based on participant capacity and purpose use of room. This suggestion is develop using rule-based system technique. Next, this system develop using agile development methodology. Agile method is known to help project on track by progress following the schedule. This method have iteration that help developers to add or change the requirement without holding off the project progress.